Forecasting the flap: predictors for pediatric lower extremity trauma reconstruction - Fallah, Kasra N.; Konty, Logan A.; Anderson, Brady J.; Cepeda Jr, Alfredo; Lamaris, Grigorios A.; Nguyen, Phuong D.; Greives, Matthew R. (Archives of Plastic Surgery, 2022)
Background Predicting the need for post-traumatic reconstruction of lower extremity injuries remains a challenge. Due to the larger volume of cases in adults than in children, the majority of the medical literature has focused on adult lower extremity reconstruction. This study evaluates predictive risk factors associated with the need for free flap reconstruction in pediatric patients following lower extremity trauma.Methods An IRB-approved retrospective chart analysis over a 5-year period (January 1, 2012 to December 31, 2017) was performed, including all pediatric patients (<18 years old) diagnosed with one or more lower extremity wounds. Patient demographics, trauma information, and operative information were reviewed. The statistical analysis consisted of univariate and multivariate regression models to identify predictor variables associated with free flap reconstruction.Results In total, 1,821 patients were identified who fit our search criteria, of whom 41 patients (2.25%) required free flap reconstruction, 65 patients (3.57%) required local flap reconstruction, and 19 patients (1.04%) required skin graft reconstruction. We determined that older age (odds ratio [OR], 1.134; P =0.002), all-terrain vehicle accidents (OR, 6.698; P<0.001), and trauma team activation (OR, 2.443; P=0.034) were associated with the need for free flap reconstruction following lower extremity trauma in our pediatric population.Conclusions Our study demonstrates a higher likelihood of free flap reconstruction in older pediatric patients, those involved in all-terrain vehicle accidents, and cases involving activation of the trauma team. This information can be implemented to help develop an early risk calculator that defines the need for complex lower extremity reconstruction in the pediatric population.
Keywords: Pediatric; Trauma; Predictive factors; Lower extremity reconstruction; Free flap